Comparison of two VA laboratory data repositories indicates that missing data vary despite originating from the same source. - McGinnis, Kathleen A; Skanderson, Melissa; Levin, Forrest L; Brandt, Cynthia; Erdos, Joseph; Justice, Amy C (Medical care, 2009)
Assessing accuracy and completeness of data is an important component of conducting research. VA Healthcare System benefits from a highly developed electronic medical information system. The Immunology Case Registry was designed to monitor costs and quality of HIV care. The Decision Support System was developed to monitor utilization and costs of veterans in care. Because these systems extract data from the same source using independent methods, they provide an opportunity to compare the accuracy and completeness of each.
Keywords: Alanine Transaminase; Aspartate Aminotransferases; Clinical Laboratory Information Systems; Cohort Studies; Creatinine; Health Care Costs; Hemoglobin A, Glycosylated; HIV Seropositivity; Hospitals, Veterans; Humans; Laboratories, Hospital; Leukocytes; Medical Records Systems, Computerized; Quality of Health Care; Reference Standards; Registries; Research Design; Systems Integration; United States; United States Department of Veterans Affairs; Viral Load